Antibacterial effects of 18 medicinal plants used by the Khyang tribe in Bangladesh - Hossan, Md Shahadat; Jindal, Hassan Mahmood; Maisha, Sarah; Samudi, Chandramathi; Sekaran, Shamala Devi; Nissapatorn, Veeranoot; Kaharudin, Fatima; Su Yi, Lim; Khoo, Teng Jin; Rahmatullah, Mohammed; Wiart, Christophe (Taylor & Francis, 2018)
Context: The resistance of bacteria to antibiotics is raising serious concern globally. Asian medicinal plants could improve the current treatment strategies for bacterial infections. The antibacterial properties of medicinal plants used by the Khyang tribe in Bangladesh have not been investigated. Objective: The present study examines the antibacterial properties of 18 medicinal plants used by the Khyang tribe in day-to-day practice against human pathogenic bacteria. Materials and methods: Leaves, bark, fruits, seeds, roots and rhizomes from collected plants were successively extracted with hexane, ethyl acetate and ethanol. The corresponding 54 extracts were tested against six human pathogenic bacteria by broth microdilution assay. The antibacterial mode of actions of phytoconstituents and their synergistic effect with vancomycin and cefotaxime towards MRSA was determined by time-killing assay and synergistic interaction assay, respectively. Results and discussion: Hexane extract of bark of Cinnamomum cassia (L.) J. Presl. (Lauraceae) inhibited the growth of MRSA, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae andAcinetobacter baumannii with MIC values below 100 µg/mL. From this plant, cinnamaldehyde evoked at 4 × MIC in 1 h an irreversible decrease of MRSA count Log10 (CFU/mL) from 6 to 0, and was synergistic with vancomycin for MRSA with fractional inhibitory concentration index of 0.3. Conclusions: Our study provides evidence that the medicinal plants in Bangladesh have high potential to improve the current treatment strategies for bacterial infection.